2017
DOI: 10.1016/j.mad.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cancer—Incidence, prevalence and mortality in the oldest-old. A comprehensive review

Abstract: Chronic health conditions are commonplace in older populations. The process of aging impacts many of the world's top health concerns. With the average life expectancy continuing to climb, understanding patterns of morbidity in aging populations has become progressively more important. Cancer is an age-related disease, whose risk has been proven to increase with age. Limited information is published about the epidemiology of cancer and the cancer contribution to mortality in the 85+ age group, often referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 82 publications
1
40
1
1
Order By: Relevance
“…The previous analysis of the B-PROOF study showed that curves for cancer incidence separated shortly after the start of the intervention, which may imply that the effect of the treatment was on cancer progression rather that cancer induction. Because our previous analysis of the B-PROOF study showed a higher risk in persons aged >80 y (24), and given that the results of this study showed that 18 of the 28 excess cancers were colorectal cancer, it may be argued that the older age group has a higher prevalence of latent colorectal neoplastic cells (8) because the risk of colorectal cancer increases with advanced age (34) and older individuals may, therefore, be more prone to the effects of folic acid and vitamin B12 supplementation. However, we did not have data on the presence of early neoplastic lesions in the colorectal mucosa to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 74%
“…The previous analysis of the B-PROOF study showed that curves for cancer incidence separated shortly after the start of the intervention, which may imply that the effect of the treatment was on cancer progression rather that cancer induction. Because our previous analysis of the B-PROOF study showed a higher risk in persons aged >80 y (24), and given that the results of this study showed that 18 of the 28 excess cancers were colorectal cancer, it may be argued that the older age group has a higher prevalence of latent colorectal neoplastic cells (8) because the risk of colorectal cancer increases with advanced age (34) and older individuals may, therefore, be more prone to the effects of folic acid and vitamin B12 supplementation. However, we did not have data on the presence of early neoplastic lesions in the colorectal mucosa to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, older population with good health and longevity has been investigated to characterize healthy aging phenotypes and differences compared to those with same age or younger to provide better public health care [ 48 51 ]. Nolen et al have published a comprehensive review on cancer prevalence in the oldest-old population and found that centenarians and the oldest-old have lower risk of cancer [ 50 ]. In Japan, where there is a relatively high population of centenarians, the Okinawa Centenarian Study, the world's longest-running population-based study of centenarians, has been performed to understand the contribution of genetic and environmental factors to exceptional longevity [ 18 ].…”
Section: Healthy Traits Of Long-lived Populationmentioning
confidence: 99%
“…Interestingly, these studies commonly concluded that not all elder people showed higher degree of age-associated disorders. In fact, long-lived individuals with inherited predisposition and their offspring showed beneficial profiles of major disabilities [ 18 , 48 50 , 52 , 53 ]. However, understanding about the effect of genetic factors on longevity is still limited.…”
Section: Healthy Traits Of Long-lived Populationmentioning
confidence: 99%
“…Tal conjuntura é potenciada por fatores de natureza biológica e social, nomeadamente a incidência mais elevada de cancro em faixas etárias avançadas (Globocan, 2012;Nolen et al, 2017) e o perfil marcadamente paternalista da relação médico-doente (Kaba e Sooriakumaran, 2007), em particular junto da população idosa. Acresce a este o facto desta categoria frequentemente possuir menores recursos pessoais, escolares, económicos e sociais, o que fomenta uma atitude de delegação no médico na condução da doença 3 , e, por consequência, inibe a (co)gestão individual na respetiva história (Silva, 2013).…”
unclassified